USIA CEO DAN KINERJA PERUSAHAAN - Setiawan, Rahmat; Gestanti, Lila (JUIMA : JURNAL ILMU MANAJEMEN, 2019)
This research analyzed the effect of CEO's age with MBA degree on firm performance and controlled with firm size, capital expenditure and firm age. Using 61 manufacturing companies that listed on Indonesia stock exchange during 2013-2017. This research analyzed with multiple linear regression. The result show that CEO's age negatively significant affect return on asset; firm size, capital expenditure, firm age positively significant affect return on asset.